PERAN CAMAT SELAKU PEMBINA DAN PENGAWAS PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA DI KECAMATAN SUKOREJO KABUPATEN PASURUAN - Istibsyaroh, Istibsyaroh (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
The sub-district head as part of the regional apparatus has the task of coaching and supervising the management of village finances. Based on the Pasuruan Regent’s Regulations regarding the delegation of the Regent’s authority to the Subdistrict Head, the subdistrict Head’s duties are very important for the Village Government. The role of the sub-district head in the form of facilitation, consultation, recommendations and evaluation of village financial management must be truly carried out by the sub-district head to prevent the village from misuse of the village budget. This research uses qualitative approach with interview, documentation and observation methods. Apart from that, researchers also looked at several documents and records held by the District. The results of this research show that the sub-district head is carrying out his role as Trustees and supervisors are mostly represented by staff in charge of Finance Village so that the Village government feels dissatisfied because of the staff in charge of village finances is considered less competent.